RESEARCH OF THE EXISTING SYSTEM OF DEVELOPMENT AND IMPLEMENTATION OF INVESTMENT-CONSTRUCTION PROJECTS - V. Opekunov; I. Shherbinin (Вестник университета)
The conducted research has shown that the system for development and realization of investment-construction project is the dicult system that consists of a set of the interconnected components and elements which directly or indirectly exert impact on key indicators of the investment-construction project: terms, cost and quality. An important component of this system is the stage of preparation of initial permissive documentation. The construction start dates directly depend on initial permissive documentation and the implementation of the project is impossible without it.